The nuclear future - Mandelbaum, Michael (Cornell studies in security affairs., 1983)
While specifically defining many of the technical terms that have made this subject so inaccessible, Michael Mandelbaum discusses the weapons systems and nuclear doctrine of both the United States and the Soviet Union along with their predicted impact on the future of the arms race.